NAHI MUNGKAR DALAM DAKWAH (Konstruksi Hadis Dakwah Terhadap Pengembangan Dakwah) - AZIZ, ABD.; SANTOSO, BOBBY RACHMAN (TASAMUH, 2020)
In Islam, activity of da’wah is not only invite the public to kindness but also prevent the people from nahi munkar. In that practice, dai puts forward the encouragement of kindness rather than nahi munkar. The reason is that nahi munkar be more risk in da'wah. Even though nahi munkar is a more important obligation in da'wah. The Prophet Muhammad practiced nahi munkar by giving priority to methods through hands, oral and heart. Nahi munkar in da'wah is always related to community norms and traditions. Therefore, dai can endure impossible by knowing the various types of mad’u. Dai will face a different mad'u in tradition, religious understanding, mastery of science and level of intelligence. Of course the measurement of truth in munkar is al-Quran, Hadis and the understanding of ulama, not on the basic of personal understanding.